Factors associated with preferred place of death among older adults: a qualitative interview study in Tama City, Tokyo, Japan - Hirotaka Onishi; Tomoya Tsuchida; Yoshifumi Ono; Aco Machino; Fumiko Inoue; Manabu Kamegai (BMJ Open)
Objectives To analyse the cognitive processes involved in the decision-making of older adults who are not in the end-of-life stage regarding the selection of a preferred place of death.Design A qualitative cross-sectional study based on semistructured in-depth interviews. The interview scripts were sectioned by context, then summarised, conceptualised and categorised. Post-categorisation, the relationships between the conceptual factors were examined.Setting Tama City, Tokyo, Japan, from November 2015 to March 2016.Participants 20 long-term care users and their families or care providers were interviewed about their preferred places of death and the factors behind their decisions.Results Three categories based on the preferred place of end-of-life care and death were extracted from the interview transcripts: (A) discouraging the decision of a preferred place of death, (B) enhancing the desire for home death and (C) enhancing the desire for a hospital/long-term care facility death. Category A consists of concerns about the caregiver’s health, anxiety about solitary death, and constraints of and concerns about the household budget. Both categories B and C consist of subcategories of reinforcing and inhibiting factors of whether to desire a home death or a hospital/long-term care facility death. If their previous experiences with care at home, a hospital or a care facility were positive, they preferred the death in the same setting. If those experiences were negative, they tend to avoid the death in the same setting.Conclusions One’s mindset and decision regarding a preferred place of death include the consideration of economic factors, concerns for caregivers, and experiences of care at home or in a hospital/long-term care facility. Furthermore, health professionals need to be aware of the ambivalence of senior citizens to support their end-of-life decisions.